Human capital and economic development - Robert Tamura (Federal Reserve Bank of Atlanta, 2002)
This paper develops a general equilibrium model of fertility and human capital investment under uncertainty. Uncertainty exists in the form of a probability that a young adult does not survive to old age. Parents maximize expected utility arising from own consumption, their fertility, and the discounted utility of future generations. There exists a precautionary demand for children. Young adult mortality is negatively related to the average human capital of young adults. Therefore, rising human capital leads to falling mortality, which eventually induces a demographic transition and an acceleration in human capital investment. The model can fit data on world and country populations, per capita incomes, age at entry into the labor force, total fertility rates, life expectancy, conditional life expectancy, and infant mortality.
Keywords: 330; Economic development; Human capital